"Stops walking when talking" as a predictor of falls in people with stroke living in the community. Issue 7 (16th June 2004) - Hyndman, D; Ashburn, A
Abstract : Objective: To test "Stops walking when talking" (SWWT) as a predictor of falls among people with stroke living in the community. Methods: People with stroke were identified through hospital records. Mobility, ADL (activites of daily living) ability, mental state, mood, and SWWT were assessed in a single session. Participants were followed prospectively for six months, using falls diaries and regular telephone calls. Results: Sixty three participants (36 men, 27 women; mean (SD) age 68.4 (10.6)) were recruited. Four subjects had a brainstem lesion, 30 had right hemisphere, and 29 left hemisphere infarctions. Mean time since onset of stroke was 20 months (range 2–72). Twenty six subjects stopped walking when a conversation was started and 16 of them fell during the six month follow up period (11 experienced repeated falls). For all fallers (⩾1) the positive predictive value of SWWT was 62% (16/26), the negative predictive value 62% (23/37), specificity 70% (23/33) and sensitivity 53% (16/30). For repeat fallers (⩾2) the positive predictive value of SWWT was 42% (11/26), the negative predictive value 89% (33/37), specificity 69% (33/48) and sensitivity 73% (11/15). Those who stopped walking were significantly more disabled (p<0.001)—that is, they were more dependent in activities of daily living, had worse gross function as well as worse upper and lower limb function, and had depression (p = 0.012). Conclusions: The specificity of the SWWT test was lower but sensitivity was higher than previously reported. Although the SWWT test was easy to use, its clinical usefulness as a single indicator of fall risk in identifying those community dwelling people with stroke most at risk of falls and in need of therapeutic intervention is questionable.